Occupational-related Stress among University Faculty Staff in Kwara State, Nigeria: Outcomes on Goal Achievement - Atunde, Martins Olanrewaju; Medupin, Johnson Abiodun; Alabi, Saliu Ishaq; Tijani, Abdulganiyu Adebayo; Awarun, Olabode; Oladejobi, Janet Oluwakemi; Oladimeji, Rasheedat Modupe; Maiye, Christiana Abosede (Quest Journal of Management and Social Sciences, 2020)
Background: Incidents of occupational stress among academicians globally is on the rise, despite its impending effects and prospects of coping strategies suggested in literature. Objective: This study examines occupational stress among university faculty staff and its outcomes on university goal achievements in Kwara State, Nigeria. Methods: The study was a cross-sectional survey. A multi-stage sampling technique was used for the selection of 458 faculty staff. Data were collected with the use of a 57-item questionnaire. Results: Results reveal that the level of stress among faculty staff was high (3.25), while stress level differs based on gender (p<.05), age (p<.01), marital status (p<.01), work experience (p<.05) and ownership of workplace (p<.05). The prominent risk associated with occupational-related stress are organizational-related (cluster mean 3.26) and role-related (CM 3.26) factors. Findings further indicate that the social support (CM 3.00) and individual-focused (CM 2.91) coping strategies were moderately adopted for managing occupational-related stress among university faculty, while the organizational support coping strategy was utilized to a low extent (CM 2.47). Conclusion and Recommendation: The study findings implicate the attainment of university goals in terms of delivering quality teaching, research and promoting scholarship and community service. Thus, the mitigation of occupational-related stress requires individual, social and most especially workplace-level interventions. Implications: The research would enable university administrators in designing appropriate workplace policies and intervention strategies or programmes for minimizing high-stress level, risk factors and their attendant effects so that faculty staff can cope effectively with work demands for the enhanced achievements of university goals.